Pengaruh Perawatan Bayi Lekat Terhadap Pencapaian Pertumbuhan Bayi Berat Lahir Rendah Di RS DR. Sardjito Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Abstract: Background: In conventional care method, a low birth weight infants (LBWi) needs an incubator or even radiant heater to prevent hypothermic and improves its general condition, but both devices are so costly that a new way of nursing called kangaroo mother care (KMC) is developed. Objective: To determine the influence of KMC and the difference in growth achievement between LBWi nursed with KMC and the others with conventional method up to the age of three months. Methods: The study was a quasi experiment with Non-Equivalent Control Group design, carried out at DR Sardjito Hospital Yogyakarta. The sample consists of pairs of Mother-LBWi, chosen using consecutive sampling were divided into two groups of treatment group and control group. Data analysis was conducted by using SPSS program. Results: The mean z score of weight for age was â 1,193 Â± 0,600 (treatment group) and â 1,308 Â± 0,586 (control group), (mean difference: 0, 1159